Reliability Analysis of Manufacturing Plant via Fault Tree Analysis: An Efficient Method for Analyzing System Reliability in Manufacturing Plants (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Fault Tree Analysis (FTA) is a graphical and logical way that focused on the failure mode of the system. This method analyze the probability of an admissible event resulting from combination and sequences of faults. A Redundancy Allocation Problem (RAP) is solved with the help of FTA in this paper. RAP is a NP hard problem (Chern, 1992) which estimate system reliability under given constraints. The goal of this paper is to analyze the reliability of the system using FTA. This method is easy to understand and there is no need of mathematical modeling so this method is more efficient comparatively other methods.